Psychological Capital Training Effectiveness to Reduce Academic Burnout Industrial Engineering Dual Role Students - Fitria Sari, Nimas Putri; Hasanah, Muhimmatul; Alfinuha, Setyani (Universitas Mercu Buana Yogyakarta, 2022)
Increased rhythm of dual role student activity results in role conflict, caused dual role student need to fulfillment of demands from two sides of activitiesÂ that have different goals. Based on initial interview we found industrial engineering dual role students have qualified for academic burnout dimention: exhaustion, cynicism, and diminished personal accomplishment.Â This research is very important with purpose to prove psychological training effectiveness to reduce academic burnout for dual role students. This research is part of quantitative methode with experimental approach use one group pretest-posttest design with psychological capital intervention as independent variable. From the research sample, 8 people of the industrial engineering dual role students were determined.